Synthesis and Characterization of Silver Nanoparticles using Aqueous Extract of Citrus maxima Leaf - Basumatary, Sanjay; Changmai, Nabajeet (Asian Journal of Chemistry, 2018)
Plant-based synthesis of silver nanoparticles is an environmental friendly method which is gaining increasing attention among the researchers as plants are readily available, non-toxic, safe to handle, cost-effective and possess a wide variability of secondary metabolites which act as both natural reducing and capping agents in silver nanoparticles synthesis. In present study, silver nanoparticles have been synthesized successfully using aqueous extract of leaves of Citrus maxima Merr. Silver nanoparticles formed were characterized by ultraviolet-visible spectrophotometer, scanning electron microscopy, transmission electron microscopy, selected area electron diffraction pattern, EDX and FT-IR spectrometer. The synthesized nanoparticles are spherical in shape, polycrystalline nature and ranged from 2 to 25 nm in size. The leaf of Citrus maxima has a strong potential for environmental friendly synthesis of silver nanoparticles.